Coal gangue-powder sepiolite fiber-nano aluminum nitride composite modified asphalt mixture and preparation method thereof
Through the composite modified asphalt mixture of coal gangue-powder seafoil fiber-nanoluminium nitride, the problem of difficult performance of coal gangue waste materials in asphalt mixture is solved, and high-temperature stability, low-temperature crack resistance and Water stability extends the service life of asphalt pavement and reduces waste of natural resources and environmental pollution.
Patent Information
- Application Number
- CN202411110159.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-14
- Publication Date
- 2024-12-24
AI Technical Summary
The prior art is difficult to effectively improve the road performance of coal gangue waste materials in asphalt mixtures, and lead to waste of natural resources and environmental pollution.
Using coal gangue-powder sepiolite fiber-nanoaluminum nitride composite modified asphalt mixture, the specific raw material ratio and preparation methods include nano aluminum nitride modifier, coal gangue powder-sepiolite fiber modification The preparation of agent and composite modified asphalt is formed to form a mesh coupling structure to enhance mechanical strength and impact resistance, and to improve the high-temperature and low-temperature properties of the asphalt mixture through the synergistic action of coal gangue powder and sepiolite fibers.
It has achieved high temperature stability, low temperature crack resistance and water stability on asphalt pavement, extended service life, reduced damage to the road surface by high and low temperatures, and has a wide range of raw materials, is non-toxic and harmless, and has no pollution in the production process, which has a good economical benefit.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of road engineering materials, and specifically to a gangue-powdered sepiolite fiber-nano aluminum nitride composite modified asphalt mixture and a preparation method thereof. Background Art
[0002] China's highway construction has a history of 30 years. Among the roads that have been built, asphalt pavement accounts for more than 90% of the road pavement. With the continuous increase in road traffic volume, the increasing traffic intensity has brought severe challenges to asphalt pavement. On the other hand, new construction and maintenance of existing roads require a large amount of building materials (such as sand, gravel, asphalt, etc.) every year, resulting in the scarcity of natural resources and damage to the natural environment. At the same time, a large amount of waste materials are abandoned and piled up, with extremely low utilization rate, which is easy to cause waste of resources and environmental pollution, and is not in line with the current green environmental protection and sustainable development strategy. As one of the main pavement structure types of high-grade highways, these waste materials have a wide range of recycling and reuse space in asphalt pavement materials. Therefore, how to develop a new modified asphalt mixture based on the effective use of waste materials, while improving the road performance of asphalt mixtures to reduce or replace the use of crude asphalt, sand and gravel and other materials has become a top priority.
[0003] The information disclosed in this background technology section is only used to deepen the understanding of the background technology of the present disclosure, and should not be regarded as acknowledging or suggesting in any form that the information constitutes the prior art known to those skilled in the art. Summary of the invention
[0004] The present application provides a gangue-powdered sepiolite fiber-nano aluminum nitride composite modified asphalt mixture and a preparation method thereof, aiming to solve the technical problem that it is difficult to improve the road performance of asphalt mixture when gangue-like waste materials are used.
[0005] According to one aspect of the present disclosure, a gangue-powdered sepiolite fiber-nano aluminum nitride composite modified asphalt mixture is provided, which is made of the following raw materials in parts by weight: 100 parts of mineral material, 3 to 7 parts of asphalt, 0.05 to 0.12 parts of gangue powder, 0.02 to 0.08 parts of sepiolite fiber, 0.09 to 0.21 parts of nano aluminum nitride, and 0.013 to 0.032 parts of modifier.
[0006] In some embodiments of the present disclosure, the gangue-powdered sepiolite fiber-nano aluminum nitride composite modified asphalt mixture is made of the following raw materials in parts by weight: 100 parts of mineral material, 4 to 6 parts of asphalt, 0.05 to 0.06 parts of gangue powder, 0.03 to 0.07 parts of sepiolite fiber, 0.12 to 0.18 parts of nano aluminum nitride, and 0.018 to 0.026 parts of modifier.
[0007] In some embodiments of the present disclosure, the gangue-powdered sepiolite fiber-nano aluminum nitride composite modified asphalt mixture is made of the following raw materials in parts by weight: 100 parts of mineral material, 4.3 parts of asphalt, 0.09 parts of gangue powder, 0.035 parts of sepiolite fiber, 0.128 parts of nano aluminum nitride, and 0.019 parts of modifier.
[0008] In some embodiments of the present disclosure, the modifier is a complex phosphoric acid-type monoalkylamino phthalate coupling agent.
[0009] In some embodiments of the present disclosure, the asphalt is at least one of road petroleum asphalt, coal asphalt, SBS modified asphalt, PE modified asphalt, SBR modified asphalt, and fiber modified asphalt.
[0010] In some embodiments of the present disclosure, the mineral material consists of coarse aggregate, fine aggregate and mineral powder.
[0011] According to another aspect of the present disclosure, a method for preparing a gangue-powdered sepiolite fiber-nano aluminum nitride composite modified asphalt mixture is provided, comprising the following steps: (1) Preparation of nano-aluminum nitride modifier: prepare the raw materials according to the above weight proportions; First, the modifier is diluted with ethanol and water to a concentration of 2%. After standing for 15 to 25 minutes, nano-aluminum nitride is added and soaked for 90 to 110 minutes. Then, the mixture is dried at 50 to 70 °C to remove water and ethanol, and finally sieved.
[0012] (2) Preparation of coal gangue powder-sepiolite fiber modifier: Mix the coal gangue powder, sepiolite fiber and modifier evenly.
[0013] (3) Preparation of composite modified asphalt: Heat and melt the asphalt at a temperature of 130°C to 140°C, then add the nano aluminum nitride modifier and coal gangue powder-sepiolite fiber modifier to the base asphalt, stir evenly and heat to 150°C to 160°C; then shear the asphalt and cool it after shearing.
[0014] (4) Preparation of composite modified asphalt mixture: Mix the mineral material heated to 175°C to 180°C with the composite modified asphalt and stir them evenly.
[0015] In some embodiments of the present disclosure, in the step (3), the shearing process is: first, low-speed shearing at a shear rate of 2000-3000 rpm for 15-20 min, and then high-speed shearing at a shear rate of 6000-7000 rpm for 30-45 min.
[0016] One or more technical solutions provided in the embodiments of the present application have at least any of the following technical effects: 1. The coal gangue-powdered sepiolite fiber-nano aluminum nitride composite modified asphalt mixture of the present application is an environmentally friendly, non-toxic and non-corrosive composite asphalt mixture with excellent road performance. It can enhance the high-temperature stability, low-temperature crack resistance and water stability of asphalt pavement and extend the service life of asphalt pavement. Its raw materials are widely available, non-toxic and harmless, the production process is pollution-free and inexpensive, the preparation process is simple, the cost is low, and it has good economic benefits.
[0017] 2. The gangue-powdered sepiolite fiber-nano aluminum nitride composite modified asphalt mixture of the present application is surface pretreated with a composite phosphoric acid type monoalkylamino phthalate coupling agent solution to allow the nano aluminum nitride to be coupled with the sepiolite fiber inside the asphalt mixture to form a mesh connection structure under the coupling action of the coupling agent, thereby enhancing the mechanical strength, impact resistance and stability of the asphalt mixture. Based on the excellent synergistic effect of gangue powder, sepiolite fiber and nano aluminum nitride, under high temperature conditions, the temperature inside the road surface decreases from top to bottom, and driven by the temperature difference, the heat energy moves to the material inside the road surface, and the material absorbs heat to generate electric charge, achieving a cooling effect; under low temperature conditions, the material will absorb the free electric charge inside the road surface to generate heat to increase the temperature to achieve a heat storage effect, thereby reducing the damage to the road surface caused by high and low temperatures.
[0018] 3. In the coal gangue-powdered sepiolite fiber-nano aluminum nitride composite modified asphalt mixture of the present application, the coal gangue powder with a large specific surface area can absorb the part of the asphalt that is prone to shear flow, and the sepiolite fiber can play a role of strengthening and toughening in the mixture, continuously transmitting and releasing stress, and at the same time, the nanomaterial continuously generates charge due to heat absorption, and the three can work together to achieve a good cooling effect; in addition, the coal gangue powder and sepiolite fiber increase the proportion of asphalt mortar accordingly, and the reinforcement effect of the fiber itself dissipates the concentrated stress inside the mixture, thereby reducing the damage to the road surface caused by high and low temperatures; the compounding of the three modified materials will increase the asphalt dosage of the asphalt mixture, form a large amount of structural asphalt inside the mixture, and the asphalt mortar is relatively increased, which weakens the intrusion of water, thereby improving the water stability of the asphalt mixture. DETAILED DESCRIPTION
[0019] In order to better understand the technical solution of the present application, the above technical solution will be described in detail below in conjunction with specific implementation methods.
[0020] Unless otherwise specified, the raw materials involved in the following examples are all commercially available conventional raw materials; the preparation methods, application methods and test methods involved are all conventional methods unless otherwise specified; the instruments and equipment involved are all conventional instruments and equipment unless otherwise specified.
[0021] In the following embodiments, the gangue-powdered sepiolite fiber-nano aluminum nitride composite modified asphalt mixture includes the following preparation steps: the raw materials are configured according to the weight ratio of 100 parts of mineral material, 3 to 7 parts of asphalt, 0.05 to 0.12 parts of gangue powder, 0.02 to 0.08 parts of sepiolite fiber, 0.09 to 0.21 parts of nano aluminum nitride, and 0.013 to 0.032 parts of a modifier (composite phosphoric acid-type monoalkylamino phthalate coupling agent).
[0022] (1) Preparation of nano-aluminum nitride modifier: The modifier was first diluted with ethanol and water, the ratio of water to ethanol was 2:8, the concentration of the diluent of the modifier (composite phosphoric acid type monoalkylamino phthalate coupling agent) was 2%, and after standing for hydrolysis for 20 minutes, nano-aluminum nitride was added and soaked for 100 minutes, and then dried at 60°C to remove water and ethanol. After sieving through a 0.075 mm square hole sieve, the prepared nano-aluminum nitride modifier was obtained, wherein the volume ratio of the added nano-aluminum nitride, modifier (composite phosphoric acid type monoalkylamino phthalate coupling agent), water and ethanol was 1:0.05:0.3:1.2.
[0023] (2) Preparation of coal gangue powder-sepiolite fiber modifier: The coal gangue powder, sepiolite fiber and modifier are uniformly mixed in a ratio of 1:0.035:0.11 to obtain a coal gangue powder-sepiolite fiber modifier.
[0024] (3) Preparation of composite modified asphalt: heat and melt the base asphalt at a temperature of 130°C to 140°C, add the above-mentioned nano-aluminum nitride modifier and coal gangue powder-sepiolite fiber modifier to the molten base asphalt, stir evenly and heat to 150°C to 160°C; then use a high-speed shearing machine to shear the heated base asphalt, and then naturally cool it to obtain a composite modified asphalt of coal gangue powder, sepiolite fiber and nano-aluminum nitride.
[0025] (4) Preparation of composite modified asphalt mixture: The mineral material heated to 170°C to 175°C and the above-mentioned coal gangue powder, sepiolite fiber, and nano-aluminum nitride composite modified asphalt are mixed and stirred evenly according to conventional methods to obtain a coal gangue powder, sepiolite fiber, and nano-aluminum nitride composite modified asphalt mixture.
[0026] Wherein, in the step (3), the shearing process is: firstly low-speed shearing at a shear rate of 2000-3000 rpm for 15-20 min, and then high-speed shearing at a shear rate of 6000-7000 rpm for 30-45 min.
[0027] Example 1: A gangue-powdered sepiolite fiber-nano aluminum nitride composite modified asphalt mixture is made from the following raw materials in parts by weight: 100 parts of AC-13 type mineral material, 3 parts of SBS asphalt, 0.05 parts of gangue powder, 0.02 parts of sepiolite fiber, 0.09 parts of nano aluminum nitride, and 0.013 parts of a modifier (composite phosphoric acid type monoalkylamino phthalate coupling agent).
[0028] Example 2: A gangue-powdered sepiolite fiber-nano aluminum nitride composite modified asphalt mixture is made from the following raw materials in parts by weight: 100 parts of AC-13 type mineral material, 4 parts of coal tar, 0.065 parts of gangue powder, 0.04 parts of sepiolite fiber, 0.12 parts of nano aluminum nitride, and 0.018 parts of a modifier (composite phosphoric acid type monoalkylamino phthalate coupling agent).
[0029] Example 3: A gangue-powdered sepiolite fiber-nano aluminum nitride composite modified asphalt mixture is made from the following raw materials in parts by weight: 100 parts of AC-13 type mineral material, 5.0 parts of road petroleum asphalt, 0.07 parts of gangue powder, 0.06 parts of sepiolite fiber, 0.15 parts of nano aluminum nitride, and 0.022 parts of a modifier (composite phosphoric acid type monoalkylamino phthalate coupling agent).
[0030] Example 4: A gangue-powdered sepiolite fiber-nano aluminum nitride composite modified asphalt mixture is made from the following raw materials in parts by weight: 100 parts of AC-13 type mineral material, 5.5 parts of PE modified asphalt, 0.08 parts of gangue powder, 0.065 parts of sepiolite fiber, 0.165 parts of nano aluminum nitride, and 0.024 parts of a modifier (composite phosphoric acid type monoalkylamino phthalate coupling agent).
[0031] Example 5: A gangue-powdered sepiolite fiber-nano aluminum nitride composite modified asphalt mixture is made from the following raw materials in parts by weight: 100 parts of AC-13 type mineral material, 6 parts of SBR modified asphalt, 0.085 parts of gangue powder, 0.070 parts of sepiolite fiber, 0.18 parts of nano aluminum nitride, and 0.026 parts of a modifier (composite phosphoric acid type monoalkylamino phthalate coupling agent).
[0032] Example 6: A gangue-powdered sepiolite fiber-nano aluminum nitride composite modified asphalt mixture is made from the following raw materials in parts by weight: 100 parts of AC-13 type mineral material, 4.3 parts of fiber-modified asphalt, 0.09 parts of gangue powder, 0.035 parts of sepiolite fiber, 0.128 parts of nano aluminum nitride, and 0.019 parts of a modifier (composite phosphoric acid-type monoalkylamino phthalate coupling agent).
[0033] Example 7: A gangue-powdered sepiolite fiber-nano aluminum nitride composite modified asphalt mixture is made from the following raw materials in parts by weight: 100 parts of AC-13 type mineral material, 7 parts of road petroleum asphalt, 0.105 parts of gangue powder, 0.08 parts of sepiolite fiber, 0.21 parts of nano aluminum nitride, and 0.032 parts of a modifier (composite phosphoric acid type monoalkylamino phthalate coupling agent).
[0034] Example 8: A gangue-powdered sepiolite fiber-nano aluminum nitride composite modified asphalt mixture is made from the following raw materials in parts by weight: 100 parts of AC-13 type mineral material, 6.5 parts of SBS modified asphalt, 0.12 parts of gangue powder, 0.075 parts of sepiolite fiber, 0.065 parts of nano aluminum nitride, and 0.029 parts of a modifier (composite phosphoric acid type monoalkylamino phthalate coupling agent).
[0035] Comparative Example 1: A common asphalt mixture is made from the following raw materials in parts by weight: 100 parts of AC-13 mineral material and 4.5 parts of SBS asphalt.
[0036] The mechanical properties and durability tests were carried out on the gangue-powdered sepiolite fiber-nano aluminum nitride composite modified asphalt mixture in Examples 1-8. The test items included flexural strength test, compressive strength test, splitting tensile strength test, drying shrinkage test and freeze-thaw cycle test to test the performance of the composite modified asphalt mixture of the present application, and compared with the ordinary asphalt mixture (Comparative Example 1). The test results are shown in Table 1.
[0037] Table 1 Mechanical properties and durability test of asphalt mixture .
[0038] It can be seen from Table 1 that the dynamic stability of the composite modified asphalt mixture of the present application is much greater than that of the ordinary asphalt mixture, indicating that the high-temperature rutting resistance of the composite modified asphalt mixture is stronger than that of the ordinary asphalt mixture; the maximum flexural strain of the composite modified asphalt mixture is much greater than that of the ordinary asphalt mixture, indicating that the toughness and ductility of the composite modified asphalt mixture are stronger than those of the ordinary asphalt mixture; the residual stability and splitting strength ratio of the composite modified asphalt mixture are greater than those of the ordinary asphalt mixture, indicating that the low-temperature crack resistance and water stability of the composite modified asphalt mixture are stronger than those of the ordinary asphalt mixture.
[0039] The composite modified asphalt mixture provided in this application meets the relevant requirements of the Ministry of Transport's standard JTGF40-2004 "Technical Specifications for Highway Asphalt Pavement Construction", and its high temperature performance, low temperature performance, and water stability performance indicators are significantly higher than those of ordinary asphalt mixtures, indicating that the composite modified asphalt mixture of this application has superior road performance.
[0040] The present application has been described in detail above in conjunction with the embodiments. However, those skilled in the art will appreciate that, without departing from the concept of the present invention, the specific parameters in the above embodiments may be changed, or the relevant materials and method steps may be replaced by equivalents, thereby forming multiple specific embodiments, which are all within the common variation range of the present application and will not be described in detail one by one here.
Claims
1. A coal gangue-powdered sepiolite fiber-nano aluminum nitride composite modified asphalt mixture, characterized in that: The invention is prepared from the following raw materials in parts by weight: 100 parts of mineral material, 3-7 parts of asphalt, 0.05-0.12 parts of coal gangue powder, 0.02-0.08 parts of sepiolite fiber, 0.09-0.21 parts of nano aluminum nitride and 0.013-0.032 parts of a modifier.
2. The gangue-powdered sepiolite fiber-nano aluminum nitride composite modified asphalt mixture according to claim 1, characterized in that: The invention is prepared from the following raw materials in parts by weight: 100 parts of mineral material, 4-6 parts of asphalt, 0.05-0.06 parts of coal gangue powder, 0.03-0.07 parts of sepiolite fiber, 0.12-0.18 parts of nano aluminum nitride and 0.018-0.026 parts of a modifier.
3. The gangue-powdered sepiolite fiber-nano aluminum nitride composite modified asphalt mixture according to claim 1, characterized in that: The invention is prepared from the following raw materials in parts by weight: 100 parts of mineral material, 4.3 parts of asphalt, 0.09 parts of coal gangue powder, 0.035 parts of sepiolite fiber, 0.128 parts of nano aluminum nitride and 0.019 parts of a modifier.
4. The gangue-powdered sepiolite fiber-nano aluminum nitride composite modified asphalt mixture according to claim 1, characterized in that: The modifier is a composite phosphoric acid type monoalkylamino phthalate coupling agent.
5. The gangue-powdered sepiolite fiber-nano aluminum nitride composite modified asphalt mixture according to claim 1, characterized in that: The asphalt is at least one of road petroleum asphalt, coal asphalt, SBS modified asphalt, PE modified asphalt, SBR modified asphalt, and fiber modified asphalt.
6. The gangue-powdered sepiolite fiber-nano aluminum nitride composite modified asphalt mixture according to claim 1, characterized in that: The mineral material consists of coarse aggregate, fine aggregate and mineral powder.
7. A method for preparing the gangue-powdered sepiolite fiber-nano aluminum nitride composite modified asphalt mixture according to claim 1, characterized in that: The steps include: (1) Preparation of nano-aluminum nitride modifier: prepare the raw materials according to the weight proportions described in claim 1; first dilute the modifier with ethanol and water to a concentration of 2%, let it stand for 15 to 20 minutes, then add nano-aluminum nitride and soak for 90 to 110 minutes, then dry at 50 to 70°C to remove water and ethanol, and finally sieve; (2) Preparing a coal gangue powder-sepiolite fiber modifier: uniformly mixing the coal gangue powder, sepiolite fiber and the modifier; (3) Preparation of composite modified asphalt: heating and melting the base asphalt at a temperature of 130°C to 140°C, then adding the nano aluminum nitride modifier and the gangue powder-sepiolite fiber modifier to the base asphalt, stirring evenly and heating to 150°C to 160°C; then shearing the base asphalt and cooling it after shearing; (4) Preparation of composite modified asphalt mixture: Mix the mineral material heated to 175°C to 180°C with the composite modified asphalt and stir them evenly.
8. The preparation method according to claim 7, characterized in that In the step (3), the shearing process is: firstly low-speed shearing at a shear rate of 2000-3000 rpm for 15-20 min, and then high-speed shearing at a shear rate of 6000-7000 rpm for 30-45 min.
